Stock and bond market indices in the CARICOM sub-region : construction and use - Pemberton, Cécile ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Constructs CARICOM-wide stock and bond market indices, including stock indices for important sub sectors, based on data obtained form Barbados, Jamaica and Trinidad & Tobago.